PUSAT INFORMASI DAN KONSELING GERAKAN BEBAS NARKOBA REMAJA MUHAMMADIYAH - Agus Supriyanto; Amien Wahyudi; Irvan Budhi Handaka (Bagimu Negeri, 2018)
Drug prevention in adolescent Muhammadiyah can be implemented through a school program. School programs need to work with school counselors to establish a Skills-Based Free Drug Information and Counseling Center. The method used in Information and counseling center is (1) education, (2) training, and (3) forum discussion group. Peer guidance, peer support, and peer counseling centers with counselors on skills-based students. Cognitive, affective, and skill dimension as the main goal of the drug-free movement. Skills developed in students are open-ended questions, listening to reflection exercises, role-playing, motivational interview skills, and model stages of change.